ANALISIS FRAMING MEDIA ONLINE DALAM PEMBERITAAN MANTAN POLITIKUS PDI PERJUANGAN YANG KEMUDIAN MENDUKUNG PRABOWO SEBAGAI CALON PRESIDEN DI PEMILU TAHUN 2024 (KOMPAS DAN DETIK NEWS) - Aziz Al Majid, Aziz; Qalban, Anas Azhimi (Hujjah: Jurnal Ilmiah Komunikasi dan Penyiaran Islam, 2023)
In today's digital era, as a container that provides a place for audiences and even individuals, where they have the same interest in finding and reading information, the web is the answer to the above statement. This is in line with the rapid growth of Information Technology both in developed countries and in developing countries, namely the availability of the internet, which can be accessed anytime and from anywhere. As a new media, mass media in the form of online news can be found in Kompas and Detik News. Framing analysis needs to be known to provide a concept for the use of images in a media report, it is necessary to look at it from various points of view. In choosing a fact has two probabilities that is what can be chosen in terms of (news section), then what can be discarded (which section is not reported). This depends on how the media sees the interesting part of news. Pan and Kosicki say that framing in media discourses is a way of social awareness that involves at least three main keys, namely the source, the journalist or reporters, and the audience. This is done to attract readers to an important part of a text in the news. The units observed in a structure there are several things that can be explained. In understanding the culture that concerns the basis of human social life is regulated, while framing analysis used by translators in testing media discourse.